2012
DOI: 10.1103/physrevb.86.125137
|View full text |Cite
|
Sign up to set email alerts
|

Robust topological surface states in Sb2Te3layers as seen from the weak antilocalization effect

Abstract: Weak antilocalization and electron-electron interaction effects are investigated in Sb 2 Te 3 layers. We accomplish smooth top and bottom surfaces for the layer using molecular-beam epitaxy, as revealed by the Kiessig oscillations in the x-ray reflectivity. The two helical surface states of the layer are found to contribute identically to the weak antilocalization effect. They are left intact in spite of low mobility and high concentration of unintentionally doped holes. The magnitude of the electron-electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
68
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 42 publications
12
68
1
Order By: Relevance
“…Both samples are characterized by a clear metallic behavior, as Sb 2 Te 3 and GST featuring at least a partial degree of vacancy ordering. 14,22 Besides the expected decrease of the mobility as the temperature increases, the GST-SL sample has a factor ∼2 higher mobility compared to the GeTe-SL (gray lines and triangles). At the same time, the 3D carrier concentration, which does not change significantly as a function of temperature, is higher in the case of the GeTe-SL (n GeTe-SL = 5.91 × 10 20 cm 3 and n GST-SL = 2.78 × 10 20 cm 3 at room temperature).…”
Section: © 2017 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
“…Both samples are characterized by a clear metallic behavior, as Sb 2 Te 3 and GST featuring at least a partial degree of vacancy ordering. 14,22 Besides the expected decrease of the mobility as the temperature increases, the GST-SL sample has a factor ∼2 higher mobility compared to the GeTe-SL (gray lines and triangles). At the same time, the 3D carrier concentration, which does not change significantly as a function of temperature, is higher in the case of the GeTe-SL (n GeTe-SL = 5.91 × 10 20 cm 3 and n GST-SL = 2.78 × 10 20 cm 3 at room temperature).…”
Section: © 2017 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
“…This is also in good agreement with previous studies on these materials (see Refs. [ 10,42,[53][54][55] and references therein). Whereas for the ternary layer a value of −1.37 is extracted, which is close to −1.5 expected for three transport channel.…”
Section: Magnetotransportmentioning
confidence: 99%
“…a) Electronic mail: th.schaepers@fz-juelich. de The robustness of the TI materials to elastic scattering, or non-magnetic impurities, and surface imperfection was the subject of a few investigations, 9,10,[12][13][14] as it is important for future applications in electronics. Surface electrical transport investigations were hampered by the high density of bulk carriers usually obtained due to intrinsic defects observed in these small gap materials.…”
Section: Introductionmentioning
confidence: 99%
“…The carrier charge is positive, indicating that mainly hole conduction is occurring, as a result of the domination of Sb(Bi) vacancies and Sb(Bi) Te antisite defects in the lattice. 22 Carrier concentration and mobility for Bi 0.4 Sb 1.6 Te 3 are 7.9 9 10 18 cm À3 and 50.6 cm 2 V À1 s À1 ; the values for Sb 2 Te 3 are 1.1 9 10 19 cm À3 and 457 cm 2 V À1 s À1 , respectively, both higher than those for Bi 0.4 Sb 1.6 Te 3 . Obviously, introduction of Bi atoms simultaneously reduces carrier concentration and mobility.…”
Section: Resultsmentioning
confidence: 96%
“…High quality Bi-Sb-Te based materials with the appropriate stoichiometry have been obtained by molecular beam epitaxy (MBE), by alternate deposition of elemental layers at room temperature and subsequent annealing at 250°C, as reported by Peranio et al, 17 and by co-evaporation of elements under Te-rich conditions as reported by Jia et al 18,19 Sb 2 Te 3 , Bi 2 Te 3 , and their alloys with an amorphous-crystalline phase transition 20,21 and topological insulator properties have recently been prepared. 18,[22][23][24] A variety of special properties of V-VI compounds are sensitive to types of impurity and defects which provide charge carriers for the materials. 25,26 Hence investigation of the effect of impurities or defects on the carrier transport properties of films will contribute to better understanding of the effect of doping.…”
Section: Introductionmentioning
confidence: 99%